Better Teaching and Learning Model Character (BTL-C) to Establish Students' Pedagogical Competence - Joko Purwanto; Sigit Sugiyanto; Malim Muhammad (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
Creating a model study of Better Teaching and Learning Character (BTL-C) can help students learn with greater passion, activity, and results while assessing the model study's validity, effectiveness, and applicability. These studies are research & Development studies (R&D). Three phases of research were carried out: an examination of the BTL-C model by theoretic and professional review. Empirical testing supports the BTL-C model's empirical validity. Phased implementation to determine whether the BTL-C paradigm is useful and effective. The study's findings show that the developed model study of BTL-C integrates character items into mathematics items and is provided at the network's ICARE step of connection. A validator has verified the validity of this model, and it is backed up with test-field validation data. This methodology has also been tested regarding how well it helps students develop their character and increase their passion, activity, and learning outcomes. Implementing the BTL-C model in practice has also been evaluated through observations of the lecturer's capacity for learning in the classroom, lecturer responses to model-use amenities, and student acceptance of the lecturer-applied model. The final results show that the generated model study for the BTL-C has met all the necessary criteria and is both practical and effective. Keywords: pedagogy competence, BTL-C, ICARE, effective